Getting Creative about Elderly Housing - O’Hara, Frank (Maine Policy Review, 2003)
In his commentary on Stephen Golant’s article in this issue, Frank O’Hara notes that Golant has very successfully identified the problems of some older homeowners. However, he suggests that the solution Golant proposes—government-assisted rental housing—may apply to only a few members of the group. Moreover, very little government-subsidized rental housing is being built or planned in Maine. Using Golant’s data, O’Hara extrapolates that affordability is the primary problem for older Maine homeowners. He notes that very few are interested in the public policy alternative that would best meet their needs, namely reverse mortgages. However, he observes that older Maine homeowners are increasingly willing to sell their homes and move into multi-family settings if the attractions are there.
Keywords: Maine; affordable housing; Maine elders